2017
DOI: 10.3390/ijms18112358
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Glycosides from Convallaria majalis Whole Plants and Their Cytotoxic Activity

Abstract: Phytochemical examination of Convallaria majalis (Liliaceae) whole plants yielded 15 steroidal glycosides (1–15), including nine new compounds (4–6, 10–15) with a lycotetrose unit. The structures of the new compounds were determined using two-dimensional Nuclear magnetic resonance (NMR) analyses and chemical methods. The isolated compounds were evaluated for cytotoxicity against HL-60 human promyelocytic leukemia cells, A549 human lung adenocarcinoma cells, and HSC-4 and HSC-2 human oral squamous cell carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…According to previously reported data [42], our two isolated compounds (steroidal glycosides 1 and 2) belong to a group of C 21 steroidal glycosides. Although a wide range of pharmacological activities (including cytotoxic, anticancer, anti-inflammatory, and antitumor) of different C 21 steroidal glycosides have been documented [37,[43][44][45][46][47], no allelopathic activities of C 21 steroidal glycosides have been reported until now. Thus, this report is the first on the allelopathic activity of steroidal glycosides 1 and 2 from M. tenacissima leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previously reported data [42], our two isolated compounds (steroidal glycosides 1 and 2) belong to a group of C 21 steroidal glycosides. Although a wide range of pharmacological activities (including cytotoxic, anticancer, anti-inflammatory, and antitumor) of different C 21 steroidal glycosides have been documented [37,[43][44][45][46][47], no allelopathic activities of C 21 steroidal glycosides have been reported until now. Thus, this report is the first on the allelopathic activity of steroidal glycosides 1 and 2 from M. tenacissima leaves.…”
Section: Discussionmentioning
confidence: 99%
“…1 H and13 C-NMR data of compound 1 in CD 3 OD. Measured at 400 MHz.The molecular structure of compound 2 was determined as C45 H 70 O 15 by using HR-ESIMS at m/z 873.4659 [M + Na] + (calcd for C 45 H 70 O 15 Na 873.4612) (Figure…”
mentioning
confidence: 99%
“…Figure 2 illustrates the mean RANK value calculated for diols, tetrols and pentols. An earlier study of steroidal glycosides from Convallaria majalis showed that the introduction of polar substituents to the steroidal nuclei resulted in reduced cytotoxicity [ 32 ]. Our docking results suggest that diols (less polar) have a higher affinity to the analyzed targets than tetrols and pentols (more polar).…”
Section: Discussionmentioning
confidence: 99%
“…3 was purified by reversed-phase HPLC (Cosmosil 5C 18 -MS-Ⅱ, 20 φ × 250 mm) with 50% MeOH–1% acetic acid to obtain astragalin ( 9 , 31.0 mg, 0.0247%), rutin ( 10 , 10.0 mg, 0.0080%), and quercetin 3- O -β-cellobioside ( 11 , 14.6 mg, 0.0112%). The chemical structures of the isolated compounds were identified by a comparison of the 1 H- and 13 C- NMR spectra with References [ 2 , 19 , 20 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The chemical structures of the isolated compounds ( 1 – 11 ) are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%